Pelatihan Deteksi Dini Terserang Stroke Dengan Metode Fast Pada Lansia Di Kelurahan Sari Bunga Mas Kecamatan Lahat : Training on Early Detection of Stroke Using Fast Methods for the Elderly in Sari Bunga Mas Village, Lahat District - Kamesyworo, Kamesyworo; Haryanti, Eka; Hartati, Sri; Elviani, Yeni (Chakra Brahmanda Lentera Institute, 2024)
Stroke is a common degenerative disease in the elderly, which causes a decrease in quality of life because the elderly become dependent on various daily activities. The fatal and permanent effects of a stroke can be prevented if the patient receives prompt and appropriate medical care within 3-5 hours, known as the